Physical chemistry of foods - Walstra, Pieter (Marcel Dekker, 2011)
This resource provides effective mechanistic methods for analyzing and understanding physical and chemical behaviour in foods, and explains how to manipulate and control such behaviour during food processing, distribution and use.;Written by 23 authorities in the field, Physical Chemistry of Foods: treats factors controlling crystallization, cross-linking reactions, dispersion and surface-adsorption processes in foods and clarifies how to modify crystal size distribution, stabilize dispersions and minimize fouling; explores uptake competition between mineral nutrients - offering guidelines for efficient uptake and absorption; describes kinetic rate-controlling steps in Maillard reactions - examining how to manipulate Maillard browning; discusses how gels form and instrumental methods of following gelling processes and covers how to create gel-based textures and structures in foods; considers factors that control the behaviour of bread during dough development, proofing, and baking - showing how carbon dioxide release affects loaf expansion; and reveals how glass transitions affect rheological and kinetic behaviour and transport processes in foods - detailing how to manipulate glass transitions and product behaviour by changes in composition and water content.;Food scientists and technologists; food, agricultural and bioresource engineers; physical and surface chemists; nutritionists; and upper-level undergraduate and graduate students and industrial trainees in these disciplines will repeatedly find valuable new insights and approaches for dealing with practical and theoretical problems and a wealth of useful